Pelatihan Peningkatan Pemanfaatan dan Literasi Teknologi Informasi dalam Mendukung Mitra UMKM Salon Kecantikan - Phie Chyan; Ridnaldy Yunior Carolus (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2024)
The community services carried out are a service program to support government programs in increasing the competitiveness of MSMEs so that they can compete in today's very tight competitive situation. MSMEs in 3T areas (disadvantaged, frontier, outermost) face much more complex problems than those in relatively more developed areas. Partners in this service activity are the MSME beauty salon HNB Salon & SPA located in Nabire Regency, Central Papua. Based on the analysis carried out by the service team, partners experience problems related to the service sales process and also management, especially in terms of customer relationship management and management of marketing activities, then to help MSME partner, the service team will support the use of technology in administering the services provided at the salon in the form of salon service applications. Additionally, increasing human resource capabilities is also very much needed, especially in using various technological equipment, both hardware and software, to support salon operations. Finally, the service team also provides training on using social media to carry out digital marketing to MSME staff. Based on the evaluation of the material for the training activities, excellent results were obtained, and the partners stated that they were very helped by the material and program that the service team had provided.